Kemampuan Menyelesaikan Soal Cerita Matematika Ditinjau Dari Gaya Belajar Siswa Kelas VII - Eva Nurdiana; Ketut Sarjana; Muhammad Turmuzi; Sri Subarinah (Griya Journal of Mathematics Education and Application, 2021)
This study aims to find out the ability to solve math story problems reviewed from the learning style of grade VII students. The type of research used is descriptive research with qualitative approach. The sample class was selected using cluster random sampling techniques and obtained 32 students who were taken 25% of the population, the sample was randomly taken 8 students from each class. The samples obtained were given a study style questionnaire in order to classify the sample into visual, auditorial and kinesthetic learning style categories. The sample that was the subject of the interview and the subject given the test question was selected based on the three categories of study style, which was taken randomly 20% of the sample of each learning style. Students' ability to solve math story problems is reviewed from known learning styles through analysis of students' answers in solving number material story questions and based on interview results. The analysis technique used is descriptive statistical analysis. From the results of the study obtained: The ability to solve math story problems of students with visual learning style, auditory learning and kinesthetic learning is good criteria, less criteria,and less criteria.